Hulless Barley – A Rediscovered Source for Functional Foods Phytochemical Profile and Soluble Dietary Fibre Content in Naked Barley Varieties and Their Antioxidant Properties - Siebenhandl-Ehn, Susanne; Kinner, Mathias; Leopold, Loredana F.; Poppernitsch, Mara B.; Prückler, Michael; Wurbs, Philipp; Poisinger, Sabine; Kalas, Elisabeth; Berghofer, Emmerich; Grausgruber, Heinrich (IntechOpen, 2011)
None